Peripheral immune cell gene expression changes in advanced non-small cell lung cancer patients treated with first line combination chemotherapy. - Yung-Che Chen; Chang-Chun Hsiao; Kuang-Den Chen; Yu-Chiang Hung; Ching-Yuan Wu; Chien-Hao Lie; Shih-Feng Liu; Ming-Tse Sung; Chung-Jen Chen; Ting-Ya Wang; Jen-Chieh Chang; Petrus Tang; et al. (PLoS ONE, 2013)
Introduction Increasing evidence has shown that immune surveillance is compromised in a tumor-promoting microenvironment for patients with non-small cell lung cancer (NSCLC), and can be restored by appropriate chemotherapy. Methods To test this hypothesis, we analyzed microarray gene expression profiles of peripheral blood mononuclear cells from 30 patients with newly-diagnosed advanced stage NSCLC, and 20 age-, sex-, and co-morbidity-matched healthy controls. All the patients received a median of four courses of chemotherapy with cisplatin and gemcitabine for a 28-day cycle as first line treatment. Results Sixty-nine differentially expressed genes between the patients and controls, and 59 differentially expressed genes before and after chemotherapy were identified. The IL4 pathway was significantly enriched in both tumor progression and chemotherapy signatures. CXCR4 and IL2RG were down-regulated, while DOK2 and S100A15 were up-regulated in the patients, and expressions of all four genes were partially or totally reversed after chemotherapy. Real-time quantitative RT-PCR for the four up-regulated (S100A15, DOK2) and down-regulated (TLR7, TOP1MT) genes in the patients, and the six up-regulated (TLR7, CRISP3, TOP1MT) and down-regulated (S100A15, DOK2, IL2RG) genes after chemotherapy confirmed the validity of the microarray results. Further immunohistochemical analysis of the paraffin-embedded lung cancer tissues identified strong S100A15 nuclear staining not only in stage IV NSCLC as compared to stage IIIB NSCLC (p = 0.005), but also in patients with stable or progressive disease as compared to those with a partial response (p = 0.032). A high percentage of S100A15 nuclear stained cells (HR 1.028, p = 0.01) was the only independent factor associated with three-year overall mortality. Conclusions Our results suggest a potential role of the IL4 pathway in immune surveillance of advanced stage NSCLC, and immune potentiation of combination chemotherapy. S100A15 may serve as a potential biomarker for tumor staging, and a predictor of poor prognosis in NSCLC.